Will Organizational Variables Predict Secondary School Teachers’ Job Involvement in Ogun State, Nigeria? - Azeez, R. Olugbenga; Mabekoje, Sesan O.; Jinmi, Taofeek O.; Adenuga, R. Alaba (NIU Journal of Social Sciences, 2019)
The present study examined organisational justice, organisational politics and organisational trust as predictors of job involvement of secondary school teachers in Ogun State, Nigeria. Three were raised and answered in the study. Four hundred and fifty (450) teachers selected from public secondary schools through the use of proportional stratified and simple random sampling techniques were administered with four standardized instruments: Job Involvement Questionnaire, Organizational Trust (OTQ), Organizational justice scale and Perceived Organizational Politics Scale . The data collected were analyzed using multiple regression analysis (MRA) and the result was tested for significance at 0.005 level. The results showed that the predictor variables jointly predicted the criterion variable. Results further showed that there was relative contribution of each independent variable to the prediction. Based on the findings, it was recommended that educational managers should take into consideration teachers' interests and capabilities while assigning courses to them, since teaching courses which is interesting to them is one of the issues that result in job involvement Keywords: Organisational justice, Organisational politics, Organisational trust, Job involvement, Teachers.